European Society of Clinical Microbiology and Infectious Diseases: update of the diagnostic guidance document for Clostridium difficile infection. (1st August 2016) - Crobach, M.J.T.; Planche, T.; Eckert, C.; Barbut, F.; Terveer, E.M.; Dekkers, O.M.; Wilcox, M.H.; Kuijper, E.J.
Abstract: In 2009 the first European Society of Clinical Microbiology and Infectious Diseases (ESCMID) guideline for diagnosing Clostridium difficile infection (CDI) was launched. Since then newer tests for diagnosing CDI have become available, especially nucleic acid amplification tests. The main objectives of this update of the guidance document are to summarize the currently available evidence concerning laboratory diagnosis of CDI and to formulate and revise recommendations to optimize CDI testing. This update is essential to improve the diagnosis of CDI and to improve uniformity in CDI diagnosis for surveillance purposes among Europe. An electronic search for literature concerning the laboratory diagnosis of CDI was performed. Studies evaluating a commercial laboratory test compared to a reference test were also included in a meta-analysis. The commercial tests that were evaluated included enzyme immunoassays (EIAs) detecting glutamate dehydrogenase, EIAs detecting toxins A and B and nucleic acid amplification tests. Recommendations were formulated by an executive committee, and the strength of recommendations and quality of evidence were graded using the Grades of Recommendation Assessment, Development and Evaluation (GRADE) system. No single commercial test can be used as a stand-alone test for diagnosing CDI as a result of inadequate positive predictive values at low CDI prevalence. Therefore, the use of a two-step algorithm is recommended. Samples without free toxin detected by toxins A and B EIA but with positive glutamate dehydrogenase EIA, nucleic acid amplification test or toxigenic culture results need clinical evaluation to discern CDI from asymptomatic carriage.